Supporting Extensive Reading with ChatGPT: A Qualitative Study of Student Experiences in an EFL Context - Herdawan, Deri; Sari, Dhesi Wulan; Setyoningrum, Ari Ani Dyah (UIR Press, 2026)
This qualitative study explores the integration of ChatGPT in enhancing the success of Extensive Reading program within the context of English as a Foreign Language. A group of students (n=38) participated in the study and three books of fantasy genre were provided as reading materials. ChatGPT was introduced to assist the participants in their reading comprehension. Data were collected through semi-structured interviewed and analysed thematically. The findings revealed that initial reading interest remains a key factor in deciding ER success. However, integration of ChatGPT provided supports in reducing linguistic and interaction barriers. As a cognitive support, it helps the participants accessing reading materials aligned with their interest and reading level. As an affective support, it facilitates discussion when human interaction is limited or inducing anxiety. This study discusses the potential of implementing ChatGPT in Extensive Reading to complement teacher’s roles without diminishing them, especially in English as a Foreign Language context.